Does Paclitaxel-Carboplatin Chemotherapy in a Dose-Dense Regimen Enhance Survival of BRCA-Related Ovarian Cancer Patients?. Issue 9 (1st November 2009) - Leunen, Karin; Cadron, Isabelle; Van Gorp, Toon; Amant, Frédéric; Berteloot, Patrick; Neven, Patrick; Legius, Eric; Vergote, Ignace
Abstract : In a group of 6 BRCA -related ovarian cancer patients presenting with clinical relapse, paclitaxel-carboplatin (TC) in a dose-dense regimen was administered to evaluate the response and tolerability compared with those of the sporadic group and of the patients using a regimen administered every 3 weeks. All patients were carboplatin sensitive at the time of first relapse: 4 patients showed intermediate sensitivity (6-12 months), and 2 patients were truly carboplatin sensitive (>12 months) at first relapse and first administration of a TC dose-dense regimen. A total of 14 dose-dense regimens were administered in a median 5th line (range, 2nd-10th line). A median of 2 dose-dense regimens (range, 1-4) was given per patient. After first administration of the TC dose-dense regimen (median, 3rd line), this resulted in response in all patients: complete remission in 33% and partial remission in the remaining 67%. Furthermore, after another consecutive line of TC dose-dense regimen, 100% response (75% with partial remission and 25% with complete remission) was reached. The results are encouraging and support the observation of extreme carboplatin sensitivity of BRCA -related ovarian cancer. The use of a TC dose-dense regimen might be even more effective.